Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcell.2021.667624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methylation Status of lncRNA-MALAT1 and MicroRNA-146a on Pulmonary Function and Expression Level of COX2 in Patients With Chronic Obstructive Pulmonary Disease

Abstract: This study aimed to investigate the role of methylation of MALAT1 and miR-146a in the pathogenesis of chronic obstructive pulmonary disease (COPD). COPD patients were grouped according to their methylation status of MALAT1 and miR-146a promoters, and we found that forced vital capacity, volume that has been exhaled at the end of the first second of forced expiration, and diffusion capacity for carbon monoxide were the highest in the MALAT1 HYPO + miR-146a HYPER group and lowest in the MALAT1 HYPER + miR-146a H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As far as we know, lncRNA can inhibit the expression of miRNA to regulate gene expression and regulate physiological and pathological processes. 26 In our investigation, based on bioinformatics analysis, miR-212-5p was screened and verified to bind with LINC00599 in 16HBE cells. As an important member of the miR family, miR-212-5p has been reported to be dysregulated in a variety of human diseases, such as non-alcoholic fatty liver disease, 27 nasopharyngeal carcinoma, 28 and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, lncRNA can inhibit the expression of miRNA to regulate gene expression and regulate physiological and pathological processes. 26 In our investigation, based on bioinformatics analysis, miR-212-5p was screened and verified to bind with LINC00599 in 16HBE cells. As an important member of the miR family, miR-212-5p has been reported to be dysregulated in a variety of human diseases, such as non-alcoholic fatty liver disease, 27 nasopharyngeal carcinoma, 28 and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The hsa-let-7b-5p participated in endothelial mitochondrial dynamics and acted as a biomarker for diagnosing Parkinsonian Syndromes. 32 , 33 The hsa-miR-1-3p inhibited lung adenocarcinoma cell tumorigenesis and improved gefitinib resistance in EGFR mutant lung cancer cell. 34 , 35 Additionally, the upstream lncRNAs of two miRNAs were predicted using ENCORI database and we found six lncRNAs with the most experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In TGF-β-treated HFL-1 cells, repressing MALAT1 boosts cell proliferation and suppresses the expression of fibronectin and α-SMA (Hu et al, 2020). Another study revealed that overexpressed MALAT1 elevates cyclooxygenase two expression via inhibiting miR-146a, which can affect pulmonary functions in COPD patients (Sun et al, 2021). Liu et al indicated that high expression of MALAT1 can be served as a biomarker to predict the acute exacerbation risk and disease conditions in COPD patients (Liu et al, 2020).…”
Section: Lncrna Metastasis-associated Lung Adenocarcinoma Transcript ...mentioning
confidence: 99%